2010
DOI: 10.1007/s12665-010-0757-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of major organophosphate pesticides used in agriculture to surface water and sediment quality (Southern Caspian Sea basin, Haraz River)

Abstract: Organophosphate pesticides are compounds that are not only toxic to both humans and wildlife but also difficult to degrade under natural environmental conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(33 citation statements)
references
References 39 publications
1
31
1
Order By: Relevance
“…Almost similar results were reported in a previous study by Hossain et al (2015) in Bangladesh as they report a highest diazinon concentration of 7.86 µg/L in lake water. The highest concentrations of diazinon (9 µg/L) measured in this study was higher than the concentration range (0.0001-1.2 µg/L) reported for other sub-(tropical) countries (Leong et al, 2007;Carvalho et al, 2008;Nasrabadi et al, 2011;Rahmanikhah et al, 2011;Chowdhury et al, 2012b;Wee and Aris, 2017) and a Mediterranean country (Masiá et al, 2015).…”
Section: Physico-chemical Variables Of Water and Sedimentcontrasting
confidence: 79%
See 1 more Smart Citation
“…Almost similar results were reported in a previous study by Hossain et al (2015) in Bangladesh as they report a highest diazinon concentration of 7.86 µg/L in lake water. The highest concentrations of diazinon (9 µg/L) measured in this study was higher than the concentration range (0.0001-1.2 µg/L) reported for other sub-(tropical) countries (Leong et al, 2007;Carvalho et al, 2008;Nasrabadi et al, 2011;Rahmanikhah et al, 2011;Chowdhury et al, 2012b;Wee and Aris, 2017) and a Mediterranean country (Masiá et al, 2015).…”
Section: Physico-chemical Variables Of Water and Sedimentcontrasting
confidence: 79%
“…Due to their bioaccumulation ability, OPPs have been detected in different environmental compartments e.g. surface and ground water (Leong et al, 2007;Rahmanikhah et al, 2010;Bhattacharjee et al, 2012;Chowdhury et al, 2012a;Hossain et al, 2015;Hasanuzzaman et al, 2017), sediment (Xue et al, 2005;Abdel-Halim et al, 2006;Nasrabadi et al, 2011;Kanzari et al, 2012;Masiá et al, 2015), and aquatic organisms (Abdel-Halim et al, 2006;Aktar et al, 2009;Malhat and Nasr, 2011;Yang et al, 2012;Masiá et al, 2015;Otieno et al, 2015) in different parts of the world with concentrations ranging from 0.003 ng chlorpyrifos/L (Rahmanikhah et al, 2010) to 0.8 mg chlorpyrifos/L (Akan et al, 2014) in aqueous matrices and 40 ng diazinon/kg (Masiá et al, 2015) to 4.3 mg diazinon/kg (Akan et al, 2014) in solid matrices. OPPs have raised great concern in the scientific community due to their possible ecological risks to the aquatic ecosystems (Masiá et al, 2015;Wee and Aris, 2017), in particular to arthropod invertebrates (Maltby et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Our samples, which were placed in a debris dump for 16 months, contained about 0.001 % Na, which indicated that it contained 0.003 % salt (calculated from NaCl/Na proportion). This would be partly because of the wash-off effect of rain (Pérez-Rodríguez et al 2015;Konoplev et al 1996;Nasrabadi et al 2011). The wash-off function of fresh water was successfully confirmed with seawater-treated wood blocks (Supplementary material 4), and we think that the same washing-off procedure occurred on the debris due to rain.…”
Section: Discussionmentioning
confidence: 70%
“…Organophosphorus (OP) and organochlorine (OC) pesticides are commonly used to control crop pests and weed growth to improve agricultural yields and quality 1–4. About 300 000 tons of pesticides are sprayed on crops or applied to the soil every year, and some of these enter into the environment, especially water and soil 5.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used preconcentration methods are liquid–liquid extraction 13, solid‐phase extraction (SPE) 14–18 and solid‐phase micro‐extraction (SPME) 19. Solid‐phase micro‐extraction is a solvent‐free, inexpensive and simple extraction technique with high sensitivity 1–3, but it is commonly used to concentrate volatile gases, which limit its application scope 5. Liquid–liquid extraction is time‐consuming, expensive and environmentally unfriendly.…”
Section: Introductionmentioning
confidence: 99%